Patterns of lymph node metastasis in locally advanced cervical cancer. Issue 39 (September 2016) - Liu, Zhikai; Hu, Ke; Liu, An; Shen, Jie; Hou, Xiaorong; Lian, Xin; Sun, Shuai; Yan, Junfang; Zhang, Fuquan
Abstract : Abstract: The aim of this study was to investigate patterns and locations of lymph node metastasis in locally advanced cervical cancers. A total of 244 consecutive patients with stage IIb cervical cancer were retrospectively evaluated. Contrast-enhanced CT scans were used for lymph node grading. Lymph nodes with the shortest axis (>1 cm) were categorized as positive and those between 0.5 and 1 cm were categorized as suspicious. All lymph nodes (LNs) were also classified by their anatomic locations. Nine hundred thirty-one LNs (136 positive and 795 suspicious) were identified. Sixty-three (25.8%) patients had positive LNs, and 153 (62.7%) patients had only suspicious LNs. The metastatic pattern was predictable traveling from level 1 (external iliac, internal iliac, obturator, and mesorectum groups) through level 2 (common iliac and presacral groups) to level 3 (para-aortic groups). In most groups, LNs were located within 1.0 cm of main blood vessels. Our novel findings were: presacral LNs metastases were rare (2/244, 0.82%); the left common iliac group (LCI) had significantly more enlarged nodes than the right common iliac group ( P = 0.00); the LCI and left down-para-aortic group were further away from blood vessels than expected (1.2 cm and 1.4 cm, respectively); no additional margin was needed in anterolateral direction for external iliac groups. The lymph node metastatic patterns are relatively predicable. Different expansions from vessels should be used to include LNs for different groups. Presacral nodes metastases are rare, and further study is warranted to see whether this region can be excluded from nodal CTV.